Scientex Enterprise: friendly safety bracelet / Wan Ahmad Harishaqmi Ahmad Shuhaimi [et al.] - Ahmad Shuhaimi, Wan Ahmad Harishaqmi; Ismail, Muhammad Ali Sufian; Jahaya, Muhamad Amirul; Sodin, Muhammad Ridhwan; Ahmad Nadzri, Nukman Hakim (2018)
Scientex Enterprise is a brand new company build up from a circle of Electrical & Electronics Engineering Department from Uitm Pasir Gudang, Johor.